Long-Term Observations of Atmospheric Constituents at the First Ground-Based High-Resolution Fourier-Transform Spectrometry Observation Station in China. (March 2023) - Liu, Cheng; Sun, Youwen; Shan, Changgong; Wang, Wei; Notholt, Justus; Palm, Mathias; Yin, Hao; Tian, Yuan; Gao, Jixi; Mao, Huiqin
Abstract: Long-term observations of the volume mixing ratio (VMR) profiles and total columns of key atmospheric constituents are significant for understanding climate change and the impact of the carbon budget in China. This study provides an overview of the first ground-based high-resolution Fourier-transform spectrometry (FTS) observation station in China, which is located in Hefei, east China. The FTS observation station can observe the total columns and VMR profiles of more than 30 atmospheric constituents. Time series of some key atmospheric constituents observed at the Hefei station since 2014 have been released to the public. The major scientific achievements obtained to date at this station include spectral retrieval characterization and harmonization, investigation of the overall characteristics of key atmospheric constituents, emission estimates, satellite and chemical transport model (CTM) evaluations, and a summary of pollutant sources and transport patterns. An outlook is also presented of the envisaged plan for observations, scientific studies, and data usage at the Hefei station. China has explicitly proposed reaching a peak in its CO2 emissions by 2030 and realizing carbon neutrality by 2060. The Hefei station will provide scientific assistance to the Chinese Government for developing green economy policies and achieving carbon neutrality and the goals of the Paris Agreement.